Double diabetes as an effect modifier for adverse perinatal outcome in pregnant women with type 1 diabetes mellitus – a retrospective multicenter cohort study - Malinowska-Polubiec, Aneta; Zawiejska, Agnieszka; Romejko-Wolniewicz, Ewa; Poprawski, Grzegorz; Towpik, Iwona; Brązert, Jacek; Handziuk, Zuzanna; Czajkowski, Krzysztof (Frontiers in Endocrinology, 2023)
Double diabetes (DDiab) is defined as a T1DM coexisting with insulin resistance (IR), metabolic syndrome (MetS) and/or obesity. Little evidence explores incidence of DDiab among T1DM pregnancies and its impact on the perinatal outcomes in this population. Study aims: 1/ to explore the prevalence of DDiab in early pregnancy in the cohort of pregnant women with T1DM; 2/to examine the association between an early-pregnancy DDiab status and fetomaternal complications characteristic for T1DM in pregnancy. Material and methods: a retrospective data analysis of the multicenter cohort of N=495 pregnant women in singleton pregnancy complicated with T1DM followed from early pregnancy until delivery in three tertiary referral centres. DDiab status was defined as T1DM plus prepregnancy obesity defined as BMI≥30 kg/m2 measured at the first antenatal visit (DDiabOb), or T1DM plus prepregnancy IR defined as eGDR (estimated Glucose Disposal Rate) below the 25th centile for the cohort measured at the first antenatal visit (DDiabIR). Proportions of the adverse pregnancy outcomes were compared 1/ between DDiabOb and Non-DDiabOb and 2/ between DDiabIR and Non-DDiabIR patients. Characteristics of the study group (data presented as mean(SD) or percentage): age: 30.0(5.1) years; age when T1DM diagnosed: 17.5(8.5) years; T1DM duration: 12.0(7,9) years; microvascular complications (White classes R,F,RF): 11.9%, prepregnancy counselling: 26.6%, baseline gestational age: 10.5(4.3) weeks, prepregnancy BMI: 23.7(4.3) kg/m2; chronic hypertension: 9.1%, gestational hypertension (PIH) 10.7%, preeclampsia (PET): 3.2%; nulliparity 53.8%, smoking in pregnancy: 4.8%, eGWG: 22.4%, DDiabOB: 10.1%; DDiabIR: 25.2%; LGA: 44.0%, NICU admission: 20.8%;. Results (data from the univariate analysis given as OR(95%CI)): both DDiabOB and DDiabIR status increased the risk for eGWG [23.15 (10.82; 55.59); 3.03 (1.80; 5.08), respectively]. DDiabIR status increased the risk for PET [4.79 (1.68;14.6)], preterm delivery [1.84 (1.13; 3.21)], congenital malformation [2.15 (1.07;4.25)] and NICU hospitalization [2.2 (1.20;4.01)]. Both DDiabOB and DDiabIR accurately ruled out PET (NPV 97.3%/98.3%, accuracy: 88.3%/75.6%, respectively), congenital malformation (NPV 85.6%/88.4%, accuracy: 78.9/69.8, respectively) and perinatal mortality (NPV 98.7%/99.2%, accuracy: 88.8%/74.5%, respectively). Conclusions: 1/ Double diabetes became a frequent complication in T1DM pregnant population. 2/ Double diabetes diagnosed in early pregnancy allows for further stratification of T1DM pregnant population for additional maternal risk.